ESSM Position Statement on Surgical Treatment of Peyronie's Disease. Issue 1 (22nd November 2021) - Osmonov, Daniar; Ragheb, Ahmed; Ward, Sam; Blecher, Gideon; Falcone, Marco; Soave, Armin; Dahlem, Roland; van Renterghem, Koenraad; Christopher, Nim; Hatzichristodoulou, Georgios; Preto, Mirko; Garaffa, Giulio; et al.
Abstract: Introduction: Patients with Peyronie's disease may experience significat distress. The choice of treatment depends on a variety of factors, including the stage of the disease, the presence of pain, severity and direction of the curvature, penile length and the quality of erectile function. Aim: To review the evidence associated with surgical treatment of Peyronie's Disease and provide clinical recommendations on behalf of the European Society for Sexual Medicine. 131 peer-reviewed studies and systematic reviews, which were published from 2009 to 2019 in the English language, were included. Methods: MEDLINE, Google Scholar and EMBASE were searched for randomized clinical trials, meta-analyses, open-label prospective and retrospective studies. Main Outcome Measure: The panel provided statements on clinically relevant questions including patient involvement in the decision process, indications for surgery, choice of the approach, and the management of patient expectations. A comparison of the different grafts used in patients who have undergone plaque incision/excision and grafting in order to identify an ideal graft, has been carried out. The prevalence of postoperative complications has been summarized. Levels of evidence were provided according to the Oxford 2011 criteria and Oxford Centre for Evidence-Based Medicine recommendations. Results: In order to allow shared decision making, a patient preoperative counselling regarding the pros and cons of each intervention is recommended. In particular, adverse effects of surgical treatments should be discussed to set realistic understanding and expectations of surgical outcomes and ultimately improve postoperative satisfaction rates. Surgical treatment should be only offered in the chronic phase of the condition, when the deformity and/or degree of erectile dysfunction, prevent patients from engaging in satisfying sexual interaction, or if the deformity is the cause of severe bother. Conclusions: Current European Society for Sexual Medicine recommendations cover several aspects of Peyronie's disease treatment. These recommendations aim both to ensure patients and partners have accurate and realistic expectations of their treatment options, as well as to formulate algorithms to guide clinician management pathways. Osmonov D, Ragheb A, Ward S et al, ESSM Position Statement on Surgical Treatment of Peyronie's Disease. Sex Med 2022;10:100459.